Exposure of Medium Dose Gamma Rays and Storage Conditions Influenced the Weight Loss and Ripening of Alphonso Mango - Yadav, M. K; Patel, N. L; Chawala, S. L; Mahatma, M. K (International Journal of Sustainable Agricultural Research, 2016)
Processing of fruits through radiation, involves exposure to short wave energy to achieve a specific purpose viz. reduced the weight loss and extended the ripening. An experiment was carried out to study the effect of irradiation and storage conditions in Alphonso mango on physiological weight loss and ripening. The experiment was laid out in completely randomized block design withfactorial concept with three repetitions. There were sixteen treatment combinations of irradiation dose (I1 -0.00, I2 -0.20, I3 -0.40 and I4 -0.60 kGy) and storage temperature (S1-Ambient, S2-90C, S3-120C and S4-CA storage (120C, O2 2%, CO2 3%). The fruits were exposed to gamma radiation for different doses from the source of 60Co at Board of Radiation and Isotope Technology, Bhabha Atomic Research Centre, Mumbai. The data indicated that the fruits irradiated with 0.40 kGy gamma rays (I3) recorded significantly minimum per cent reduction in PLW and extended the ripening. Same pattern noted when fruits kept at 90C storage temperature. In combined effect of 0.40 kGy gamma rays irradiation and 90C storage temperature (I3S2) also recorded maximum reduction in the PLW and ripening per cent throughout the storage period.